Hippocampal Neurotransmitter Inhibition Suppressed During Gaming Explained by Skill Rather Than Gamer Status - Prena, Kelsey; Cheng, Hu; Newman, Sharlene D. (Frontiers in Human Neuroscience, 2020)
Goal-directed spatial decision making video games combine spatial mapping, memory, and reward; all of which can involve hippocampal excitation through suppression of an inhibitory neurotransmitter, gamma aminobutyric acid. In this study, gamma aminobutyric acid was measured before and after 30 minutes of video game play within a voxel around the hippocampus. It was predicted that all participants would experience a decrease in gamma aminobutyric acid during gaming as a result of in-game rewards. And, those who were most competitive with the goal-directed spatial decision making game would display lower hippocampal gamma aminobutyric acid concentrations after gaming. Those who were not competitive, because they were too skilled or not skilled enough, would demonstrate higher hippocampal gamma aminobutyric acid concentrations after gaming. While there were no significant differences in hippocampal GABA before and after gaming for gamers and non-gamers alike, there was a significant quadratic regression between performance on a spatial working memory task and post-gaming hippocampal gamma aminobutyric acid concentrations.